2021
DOI: 10.1093/ojls/gqaa061
|View full text |Cite
|
Sign up to set email alerts
|

Planned Obsolescence in the Context of a Holistic Legal Sphere and the Circular Economy

Abstract: Businesses may take advantage of rapid technological developments to increase sales by designing products with a short lifespan and encouraging consumers to buy a replacement more quickly than they otherwise might have to, which is commonly known as planned obsolescence. While employing a holistic approach and exploring planned obsolescence from three different angles—the demand side, supply side and environmental side—the article argues that the current measures in the fields of unfair competition and consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 0 publications
0
33
0
3
Order By: Relevance
“…According to this approach, consumers and society are made dependent and exploited, resources are wasted and significant environmental problems arise. (Sihvonen, 2020;La Rosa, 2020;Albrecht, 2019;Latouche, 2009;Proske et al, 2016;Malinauskaite and Erdem, 2021;Zhao et al, 2021;Özkan and Yücel, 2020;Marcus, 2020;Kuppelwieser et al, 2019;Paricio et al, 2019;Adrion and Woidasky, 2019). In the second approach, planned obsolescence is considered as a concept that provides various benefits to both producers and consumers and society.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this approach, consumers and society are made dependent and exploited, resources are wasted and significant environmental problems arise. (Sihvonen, 2020;La Rosa, 2020;Albrecht, 2019;Latouche, 2009;Proske et al, 2016;Malinauskaite and Erdem, 2021;Zhao et al, 2021;Özkan and Yücel, 2020;Marcus, 2020;Kuppelwieser et al, 2019;Paricio et al, 2019;Adrion and Woidasky, 2019). In the second approach, planned obsolescence is considered as a concept that provides various benefits to both producers and consumers and society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investigating the underlying reasons for the life cycle of smart phones and planned obsolescence, Proske et al (2016) found that a significant portion of consumers believed in the reality of planned obsolescence in the market and wanted to have more durable products. Malinauskaite and Erdem (2021), evaluating planned obsolescence from three different perspectives (demand side, supply side and environmental side), stated that existing measures to deal with planned obsolescence are insufficient in terms of unfair competition and consumer protection law, competition law and environmental law. They expressed the need for EU measures prohibiting planned obsolescence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…7 Mobile phone producers have been confronted with lawsuits and authority decisions about their planned obsolescence strategies (Gibbs, 2018;Vasseur, 2020). In 2017, the Italian Competition Authority (Autorità Garante della Concorrenza e del Mercato (AGCM)) imposed 5 million euro fines to Apple and Samsung for unfair commercial practices, with Apple receiving an additional 5 million euro fine for failing to properly inform consumer (Malinauskaite & Erdem, 2021). Apple argued that intentionally slowing down older iPhones via software updates was necessary to avoid unforeseen shutdowns, even though such a program would disable the utility of a device well before its physical product lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars for instance discussed the legal implications of settling to pay class action settlements in coupons valid only for purchasing products from the company that plaintiffs sued in the first place (Connolly, 2016;Gallagher, 2015). Other studies centre around the question of which legal responses-competition law, consumer protection law, environmental law or criminal law-are the most adequate to regulate planned obsolescence (La Rosa, 2020;Maitre-Ekern & Dalhammar, 2016;Malinauskaite & Erdem, 2021), or place planned obsolescence within the political and economic historical climate in which it developed (Pope, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the problem of planned obsolescence has attracted the attention of many stakeholders, including the media, community and consumer protection organizations, academics, businesses and institutions, and has been the subject of wide public debate at local and international levels [30]. One of its effects is the gradual introduction of institutional solutions aimed at combating the abuses arising in this area and improving the effectiveness of their prosecution by law [31].…”
Section: Introductionmentioning
confidence: 99%